18F-Trifluoromethylated D-Cysteine as a Promising New PET Tracer for Glioma Imaging: Comparative Analysis With MRI and Histopathology in Orthotopic C6 Models - Ma, Hui; Zhao, Jing; Liu, Shaoyu; Xie, Dingxiang; Zhang, Zhanwen; Nie, Dahong; Wen, Fuhua; Yang, Zhiyun; Tang, Ganghua (Frontiers in Oncology, 2021)
In comparison with MRI and histopathology, this study was to comprehensively explore the potential application of 18F-trifluoromethylated D-cysteine (S-[18F]CF3-D-CYS) in evaluating glioma by using orthotopic C6 glioma models. SD rats (n = 9) were implanted with C6 glioma cells. Tumor growth was monitored every week by multiparameter MRI (including DCE-MRI), [18F]FDG, S-[18F]CF3-D-CYS, and [18F]FDOPA PET imaging. Repeated scans of the same rat with the two or three [18F]-labelled radiotracers were investigated. Initial regions of interest were manually delineated on T2WI and set on the same level of PET images and tumor-to-normal ratios (TNRs) were calculated to semi-quantitatively assess the tracer accumulation in the tumor. The tumor volume in PET and histopathology was calculated. HE, and Ki-67 immunohistochemical staining was further performed. The correlations between the uptake of S-[18F]CF3-D-CYS and Ki-67 were analyzed. Dynamic S-[18F]CF3-D-CYS PET imaging showed tumor uptake rapidly reached a peak, maintained plateau during 10-30 min after injection, then decreased slowly. Compared with [18F]FDG and [18F]FDOPA PET imaging, S-[18F]CF3-D-CYS PET demonstrated the highest TNRs (P < 0.05). There were no significant differences in the tumor volume measured on S-[18F]CF3-D-CYS PET or HE specimen. Further, our results showed that the uptake of S-[18F]CF3-D-CYS was significantly positively correlated with tumor Ki67 and the poor accumulated S-[18F]CF3-D-CYS was consistent with tumor hemorrhage. Whereas there was no significant correlation between the S-[18F]CF3-D-CYS uptakes and the Ktrans values derived from DCE-MRI. In comparison with MRI and histopathology, S-[18F]CF3-D-CYS PET performs well in diagnosis and evaluation of glioma. S-[18F]CF3-D-CYS PET may serve as a valuable tool in the clinical management of gliomas.